Device Modeling of the Performance of Cu(In,Ga)Se2 Solar Cells with V-Shaped Bandgap Profiles - Shou-Yi Kuo; Ming-Yang Hsieh; Dan-Hua Hsieh; Hao-Chung Kuo; Chyong-Hua Chen; Fang-I Lai (International Journal of Photoenergy)
The effect of Cu(In,Ga)Se2 (CIGS) with V-shaped bandgap on device performance is investigated in detail. A series of Ga/(In+Ga) ratio are set to study the influence of V-shaped bandgap profile on the electricity of CIGS thin film solar cells. The modeling of device current density-voltage (J-V) curve and bandgap grading profile corresponded well to measurement results. Detailed characteristic and modeling results show that an increased gradient of bandgap from valley to the buffer layer CdS will result in a barrier and lead to an enhanced recombination in the valley. This phenomenon can be modified by the back electric field resulting from a gradient bandgap from valley (bandgap minimum) to the Mo back contact. These results indicate CIGS-based solar cells can achieve higher performance by optimizing the V-shaped bandgap profile.